(untitled) (Vietnam Journal of Community Medicine, 2025)
Teratoid Wilms tumor is a rare variant of Wilms tumor. This entity is characterized by atypical histopathological features, with the presence of various mature heterologous elements resembling those seen in teratomas, including adipose tissue, striated muscle, cartilage, glial tissue, intestinal epithelium, and respiratory epithelium. On imaging, the presence of fat within a renal mass in a pediatric patient may lead to diagnostic confusion with benign lesions such as angiomyolipoma or teratoma. We report a case of a large renal mass predominantly composed of adipose tissue, without calcification, and demonstrating poor response to chemotherapy. Initial core needle biopsy suggested a stromal-predominant Wilms tumor; however, the final diagnosis following complete surgical resection was confirmed as teratoid Wilms tumor.